Counseling cross-culturally an introduction to theory and practice for Christians - Hesselgrave, David J. (Grand Rapids, MI Baker, 1984)
Includes bibliographical references and indexes.
Keywords: Counselling -- study and teaching; Cross-cultural ministry -- study and teaching